2017
DOI: 10.1111/jonm.12541
|View full text |Cite
|
Sign up to set email alerts
|

Preceptors’ perceptions of the elements of a successful and an unsuccessful orientation period for newly graduated nurses

Abstract: Nurse leaders play an important part in ensuring newly graduated nurses have a safe nursing career starting point and, for preceptors, opportunities to provide orientation that is as good as possible. Supportive leadership, sufficient resources and good interpersonal relationships should be the leading principles during newly graduated nurses' orientation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…In terms of implications for further nursing research, the findings reinforce the need to re-study the impacts of improved orientation programs intended for newly graduated nurses. There are numerous publications (Abiodun, Daniels, Pimmer, & Chipps, 2019;Ke, Kuo, & Hung, 2017;Lindfors, Meretoja, Kaunonen, & Paavilainen, 2018;Pasila, Elo, & Kääriäinen, 2017) that synthesize and clarify the needs of newly graduated nurses in terms of orientation programs and their benefits. Using these findings, it would be possible to develop an orientation program taking into account the specific learning needs of newly graduated nurses and then assess the impacts of this program on different parameters pertaining to humanistic caring.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of implications for further nursing research, the findings reinforce the need to re-study the impacts of improved orientation programs intended for newly graduated nurses. There are numerous publications (Abiodun, Daniels, Pimmer, & Chipps, 2019;Ke, Kuo, & Hung, 2017;Lindfors, Meretoja, Kaunonen, & Paavilainen, 2018;Pasila, Elo, & Kääriäinen, 2017) that synthesize and clarify the needs of newly graduated nurses in terms of orientation programs and their benefits. Using these findings, it would be possible to develop an orientation program taking into account the specific learning needs of newly graduated nurses and then assess the impacts of this program on different parameters pertaining to humanistic caring.…”
Section: Resultsmentioning
confidence: 99%
“…Support from tenured colleagues and a welcoming and safe clinical environment where NGNs are treated similarly to everybody else creates a setting that enables NGNs to develop their professional and clinical competence. A safe nursing environment protects NGNs from burnout and premature resignation (3,20,28,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…They work as role models for NGNs by modelling professional behaviour and reflective practice and leading by example (27). The preceptor's professional know‐how, work experience, open‐mindedness and readiness for change were seen as contributory factors of the orientation (28). In their study, Rush et al (12) found that the quality of the time spent with the preceptor may be more important than the quantity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preceptor development is essential to the success of the orientation process (Barba et al, 2019;Lindfors et al, 2018). Nurse preceptors are role models and transitioning nurse orientees should set their own professional growth goals based on those models.…”
Section: Role Of the Nursementioning
confidence: 99%